2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23787
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Web-based Virtual Open Laboratory Teaching Assistant (VOLTA) for Circuits Laboratory

Abstract: A Virtual Open Laboratory Teaching Assistant (VOLTA) provides personalized instruction for students participating in a self-paced undergraduate circuits laboratory. VOLTA allows students to work in the open laboratory even when a teaching assistant is unavailable. The system's components include pre-lab testing and instruction, engineering design exercises, short topic explanation videos, instrumentation instruction (including safety), and a corresponding post-lab test module. This web-based software guides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…To observe the effect of teaching modes (in-person vs. online) on students' learning performance, students' exam grades crossing eight semesters were analysed using One-Way analysis of variance (ANOVA) via MATLAB's Statistics and Machine Learning Toolbox, particularly, the anova1() function. The One-Way ANOVA provides results to determine any statistically significant differences between the means of two or more independent samples, i.e., whether different groups of an independent variable have different effects on the response variable (Kumpass-Lenk et al, 2018;Boysen, 2015;Saleheen et al, 2015;Khan et al, 2018). In this analysis, the independent variable is the teaching mode having two levels: inperson and online.…”
Section: Student Exam Gradesmentioning
confidence: 99%
“…To observe the effect of teaching modes (in-person vs. online) on students' learning performance, students' exam grades crossing eight semesters were analysed using One-Way analysis of variance (ANOVA) via MATLAB's Statistics and Machine Learning Toolbox, particularly, the anova1() function. The One-Way ANOVA provides results to determine any statistically significant differences between the means of two or more independent samples, i.e., whether different groups of an independent variable have different effects on the response variable (Kumpass-Lenk et al, 2018;Boysen, 2015;Saleheen et al, 2015;Khan et al, 2018). In this analysis, the independent variable is the teaching mode having two levels: inperson and online.…”
Section: Student Exam Gradesmentioning
confidence: 99%
“…), and later at Georgia Tech (GT) utilizing similar dedicated lab stations that transformed into the earliest FPAA devices [29]. Additional remote systems have attempted other concepts having users log-in and control a remote computer [32][33][34][35], as well as debates over the right use of remote hardware for classes [32]. These approaches involve using a hardware board (e.g., Spartan 3 or Arduino board) and using graphical languages like Labview (e.g., [36]).…”
Section: Additional Configurable Remote Platform Considerationsmentioning
confidence: 99%
“…Equipped with pre-lab testing and instruction, engineering design exercises, short topic explanation videos, instrumentation instruction (including safety), and a corresponding post-lab test module, VOLTA is able to provide on-demand, smart assistance to students. A preliminary study on the effectiveness of VOLTA showed that the students participating in VOLTA performed slightly better compared to the control group 7 . In that experiment, the ANOVA (analysis of variance) test was run on the gain score of the students.…”
Section: Introductionmentioning
confidence: 97%
“…It is similarly not feasible to provide 7/24 support. In order to address this problem, we developed a system called the Virtual Open Laboratory Teaching Assistant (VOLTA) that provides automated on-demand instructional support 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation